LATE CRETACEOUS-CENOZOIC DEFORMATION OF NORTHEAST ASIA - Gaina C.; Müller R.D.; Roest W.R. (My University, 2002)
The plate tectonic paradigm implies rigid plates and narrow plate boundaries. In contrast, diffuse plate boundaries are common both in the oceans and continents [R.G. Gordon, Annu. Rev. Earth Planet. Sci. 26 (1998) 615–642], and their history is difficult to constrain, especially in remote, tectonically complex areas such as northeast Asia [M.E. Chapman, S.C. Solomon, J. Geophys. Res. 81 (1976) 921–930]. Here we show how extensive North Atlantic marine magnetic [R. Macnab et al., EOS 76 (1995) 449, 458] and gravity data [D.T. Sandwell, W.H.F. Smith, J. Geophys. Res. 102 (1997) 10039–10054] can be used to unravel, with tight confidence limits, successive periods of deformation over 80 million years, along the diffuse continental Eurasian–North American plate boundary. A period of compression in the Late Cretaceous (14 mm/yr in the Laptev Sea to 20 mm/yr in Kamchatka) led to thrusting in the Verkhoyansk Mountains, and was followed by extension from 68 to 40 Ma when ∼400 km of extension was accommodated by the formation of a series of grabens, including the Moma Rift system. Since 40 Ma, time-varying compression and transpression along the Moma Rift system created strike-slip faults, thrusts and folds at rates up to 6.3 mm/yr. In the Laptev Sea region, 600 km of extension from latest Late Cretaceous to present created the Laptev Sea and Lena Rift systems. The deformation predicted by our model fits most geological features formed in the Laptev Sea and central northeast Asia during Late Cretaceous–Cenozoic times. The most recent deformation (Late Miocene–Pliocene) is not very well constrained since our model lacks data younger than 11 Ma. The deformation that occurred in Kamchatka reflects a complex tectonic setting and our model’s predictions are only tentative.
Keywords: Cenozoic; Cretaceous; Cenozoic; Кайнозой; Mesozoic::Cretaceous; Мезозой::Меловая